ECONOMIC INTEGRATION: TRENDS, CRITERIA AND CONDITIONS IN THE CONTEXT OF THE 10TH ANNIVERSARY OF THE KYRGYZ REPUBLIC IN THE EURASIAN ECONOMIC UNION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article examines issues of economic integration as one of the phenomena of interstate interaction aimed at creating common conditions for the functioning of factors of production and forming a coordinated system of management of the united space. Of particular interest are the criteria and conditions for the formation of economic integration cooperation and the prerequisites for countries’ participation in international economic associations. In this regard, and in the context of the 10th anniversary of the Kyrgyz Republic’s accession to the Eurasian Economic Union (EAEU), the authors attempt to identify some patterns and characteristics of economic integration based on an analysis of international experience and individual economic integration associations.
Keywords: economic integration, international economic cooperation, criteria and conditions for integration, Kyrgyz Republic, common market, stages of integration, Eurasian Economic Union, European Union, economic security.